Concentrations and profiles of brominated diphenyl ethers (BDEs) in Baltic and Atlantic herring - Roots Ott; Zitko Vladimir; Kiviranta Hannu; Rantakokko Panu; Ruokojärvi Päivi (Oceanologia, 2009)
The total concentrations of BDEs in Baltic herring, caught in different years (2002-08) from various areas of the Baltic, and in Atlantic herring (2006) can be reasonably well described by a single concentration vs weight relationship. Samples collected a few years earlier and analysed by others show a slightly different relationship. This indicates that the weight of the fish is an important factor determining the level of contamination and that the contamination apparently did not increase between 1999 and 2008. However, two Baltic herring samples collected in 2007 contained, for reasons unknown, very high concentrations of BDE 209. The BDE profiles (concentrations scaled to a sum of 100) varied a great deal. It is impossible to determine how much of this variation is real and how much is caused by errors in the analyses. The concentration of the BDE 75 was much higher in the Atlantic than in the Baltic herring. Even after taking this into consideration, however, the BDE profile in Atlantic herring is different from the BDE profiles in Baltic herring.